Optimization of the concentric heat exchanger with injector turbulators by Taguchi method - Turgut, Emre; Cakmak, Gulsah; Yildiz, Cengiz (Pergamon-Elsevier Science Ltd, 2012)
The purpose of this study is to determine the optimum design parameters of the concentric heat exchanger with injector turbulators using Taguchi experimental design method. In the study, the effects on the heat transfer and pressure loss of the injector-shaped turbulators having different angle, diameter and number were investigated. Experiments were carried out between 10,000 and 17,000 values of Reynolds number. This study analyzed five experimental parameters affecting the heat transfer and pressure loss of concentric heat exchanger with turbulators using the Taguchi method. So, the L(16) (4(2) X 2(3)) orthogonal arrays consisting of these parameters were selected for experimental design. The effective parameters on the heat transfer and pressure loss were ordered as Reynolds number, number of injector, injector angle, diameter of injector and arranging type, respectively. Finally, it was found that the optimum operating condition for the heat transfer and the pressure loss. The results also proved that the Taguchi experimental design method was successfully applied in the study and numerical and experimental results were in very good agreement with each other. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Taguchi Method; Injector turbulators; Concentric heat exchanger; Optimization